Adverse events of androgen receptor pathway inhibitors in prostate cancer from real world data - Jongsoo Lee; Miho Song; Subeen Leem; Jong-Yeup Kim; Benjamin I. Chung; Sung Ryul Shim; Jae Heon Kim (PLoS ONE, 2025)
Purpose While clinical RCTs have clearly evidenced that the use of androgen receptor pathway inhibitor (ARPI)s for patients with advanced prostate cancer, can significantly delay disease progression, there is insufficient evidence on their safety profiles to warrant their unqualified implementation as the treatment of choice or with which to choose between them. We aim to provide more substantial evidence for adverse event (AE)s of ARPI by analyzing real-world data (RWD) to select optimal ARPI for individual treatment. Materials and Methods We used data from the Food and Drug Administration Adverse Event Reporting System (FAERS) in the US, between April 30, 2014 and April 30, 2024. Results We estimated proportional risk ratio (PRR)s of AEs in the US. We also compared the likelihood of AEs by age, reporter type, and ARPI groups: 1) Group 1, Enzalutamide with other medications; 2) Group 2, Apalutamide with other medications; 3) Group 3, Darolutamide with other medications; 4) Group 4, Abiraterone with other medications; 5) Group 5, Abiraterone + Enzalutamide with other medications. We identified 107,582 AEs among 44,856 US residents who were treated with ARPIs for prostate cancer. By ARPI groups, the AE of GI was the highest in Group 1 and Group 3, and the AE of vascular was the highest in Group 4 and Group 5. In particular, Group 2 showed very statistically significantly higher levels of PRR 3.558 (95%CI: 3.489–3.627) of skin-related AE compared to other groups. Conclusion Our study provides important insight that we analyzed RWD and evaluated comparative drug safety across all type of prostate cancer. Although we could not make a conclusion whether which is the safest ARPI, we can suggest that each ARPIs have different types of AEs hence we can use this information during choosing ARPIs for prostate cancer patients.